Arteriografia encefálica em gatos sem raça definida (Felis silvestris catus) - Moraes Júnior, Cláudio Eustáquio de (2018)
Arteriography is a radiographic examination using contrast to visualize structures that could not be identified on conventional radiography. For cerebral vasculature it is of great importance mainly for the identification of ischemic and hemorrhagic lesions. The purpose of this study was to evaluate the efficacy of the angiography technique with the meglumine ioxitalamate test to demonstrate the normal angiographic pattern and to contribute to the diagnosis of vascular alterations. Ten adult cats were used for the surgical catheterization of the right common carotid artery and administration of 6.0 ml of contrast medium, 3.0 ml for the right lateral-lateral projection and 3.0 ml for the ventro-dorsal skull projection. The right middle cerebral artery was identified in the right lateral cerebral artery and in the ventro-dorsal projection the right internal carotid arteries and the right middle cerebral artery. Renal function was assessed by measuring urea and creatinine at three times (24 hours pre-operatively, 24 hours post-operatively and seven postoperative days). There was no statistical difference between the times (p-value creatinine = 0.2831 , p-value urea = 0.6848).